Association between emergency caesarean section, earlier order of birth, high parental age gap and autism spectrum disorder among Malaysian children: a case-control study - Galvan, Jo Ann Andoy; Ramalingam, Prabhagari Nair; Patil, Sapna Shridhar; Shobri, Muhammad Aminul Syahmi; Chidambaram, Kumarappan; Sahrir, Muhammad Sabri; Chinna, Karuthan (Universiti Malaysia Sabah, 2019)
A rise in the prevalence of autism spectrum disorders in the last decades led recent research to focus on the diagnosis comparing environmental and genetic factors. This paper sought for possible factors that put children at risk for ASD. We investigated the association of ASD with the following independent factors: parental ages, parental age gaps, and birth order and birth delivery method among the Malaysian population. We recruited 929 children from primary national schools enrolled during the academic year 2017-2018 that with 465 cases and 464 controls. Questionnaires were distributed to the parents of these children and data analysed using SPSS version 20. Significant associations were found on three variables: mode of delivery (p <0.01), birth order (p < 0.001) and parental age gap (p<0.05). Emergency Caesarean section (OR = 1.55, 95% CI [1.13, 2.26]), earlier order of birth in the family (OR = 1.45, 95% CI [1.28-1.61]) and increasing gap in parental ages (OR = 1.04, 95% CI [1.001, 1.07]) were positively associated with ASD. This study concludes that emergency Caesarean section, earlier order of birth in the family and increasing gap in parental age are independent risk factors in the development of autism among primary school children in Malaysia.